Analisis Implementasi Perda Kab. Deli Serdang Nomor 4 Tahun 2021 Tentang Pengelolaan Sampah (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Deli Serdang Regency Regional Regulation Number 4 of 2021 concerning Waste Management is a regional regulation which aims to create a Deli Serdang Regency that is clean, neat, cool and shady. Current human activities cannot be separated from producing organic and non-organic waste, which if not managed properly can cause visual disturbances, threats to public health, and environmental pollution. This research aims to analyze the extent of implementation of Deli Serdang Regency Regional Regulation Number 4 of 2021 concerning Waste Management. This research uses quantitative and qualitative research methods. Quantitative methods were used to analyze data from questionnaires distributed to the public and cleaning staff. Qualitative methods were used to analyze data from observations made at several waste management locations in Deli Serdang Regency. The results of the research show that the implementation of the Deli Serdang Regency Regional Regulation, especially No. 4 of 2021 regarding waste management, can be said to have not been implemented optimally. This is because from observations made and also surveys through distributing questionnaires to the community, it was found that there are still many people in VIII Medan Estate hamlet, most of whom are still unaware of the existence of regulations governing waste management. As a result, local community participation decreases and the community may not be involved in activities such as socialization related to waste management.